Pengelolaan Sistem Syari’ah dalam Meningkatkan Jumlah Unit Usaha di Pesantren At-Tahdzib Jombang - Asyarurahim; Febi Ambarwati (J-Mabes: Jurnal Manajemen, Akuntansi, Bisnis dan Studi Ekonomi Syariah, 2024)
Islamic boarding school is an institution that has a lot of potential, including economic potential. To increase this potential is a challenge for Islamic boarding schools so that they can improve the economic welfare of the Islamic boarding school itself and the wider community. The spirit of independence that is formed by students can be a potential for Islamic boarding schools to increase the economic stability of Islamic boarding schools. One of the efforts to make the Attahdzib Islamic boarding school independent is through business units. Where a well-organized business will provide output with good income. In today's era of free competition, building the competency and capacity of students is a must. Many Islamic boarding schools have tried to develop productive economic activitiesThe existence of these various business units is a means of education in the fields of independence, entrepreneurship, sincerity and sacrifice Based on the limitations and identification of problems that have been determined, the formulation of the problem is how is the management applied by sharia business units in increasing the number of business units in the At-Tahdzib Islamic boarding school? The problem approach used in this study is to use a type of field research where data is obtained from the field directly from the source, so that the data sources in field research are primary and secondary sources.  Through a qualitative approach, namely research used to research natural or natural social life. Based on the results of the presentation and analysis of data, the author obtained a conclusion that can be drawn from the research on "Sharia Business Unit Management in Increasing the Number of Business Units in the At-Tahdzib Jombang Islamic Boarding School" is the value-based management of the Islamic boarding school, implementing the Vision and Mission of the At-Tahdzib Islamic Boarding School which is the basis for the movement of business unit management run by the At-Tahdzib Islamic Boarding School. Vision, Mission of At-Tahdzib Islamic Boarding School to Become a Solid Salaf Islamic Boarding School with Pillars of Noble Morals and Spiritual-Emotional-Intellectual Intelligence", as well as the goal of the pesantren which is a strength in all activities, which is the foundation of the soul of all residents of the pesantren as a sustainable pesantren program.